2017
DOI: 10.1590/0102-6720201700010011
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Computed Tomography Volumetry and Graft Weight Estimation in Adult Living Donor Liver Transplantation

Abstract: Background:Computed tomography volumetry (CTV) is a useful tool for predicting graft weights (GW) for living donor liver transplantation (LDLT). Few studies have examined the correlation between CTV and GW in normal liver parenchyma. Aim:To analyze the correlation between CTV and GW in an adult LDLT population and provide a systematic review of the existing mathematical models to calculate partial liver graft weight. Methods:Between January 2009 and January 2013, 28 consecutive donors undergoing right hepatect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous studies reported a significant correlation between the predicted liver volume and the actual volume, or the actual weight of the liver. 16,20 Unfortunately, most of the data were derived from healthy liver grafts of living donors. There was a study on CT volumetry in patients who underwent partial liver resection; however, this study did not take the presence of liver cirrhosis into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported a significant correlation between the predicted liver volume and the actual volume, or the actual weight of the liver. 16,20 Unfortunately, most of the data were derived from healthy liver grafts of living donors. There was a study on CT volumetry in patients who underwent partial liver resection; however, this study did not take the presence of liver cirrhosis into account.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies suggested that this number might not be appropriate, and alternative methodsranging from a different conversion factor to a more complex formula-were proposed. 16,19,20,25 Nevertheless, these suggestions came from studying normal livers and did not account for the presence of liver cirrhosis. In the current study, we proposed a formula that can accurately predict the weight of the resected cirrhotic liver (R-squared =0.914).…”
Section: Discussionmentioning
confidence: 99%
“…These include various computer programs, 12 decreasing CT slice thickness and different equations and formulas using patient's age, height, gender, body weight, BSA, and even maximal portal vein diameters. 8,13 It is however recognized that universal applicability of such proposed methods is questionable due to several factors. 14 Although CT scan with manual volumetry is gold standard for assessment of liver volumes, it overestimated the graft weight in most of the cases of our study.…”
Section: Discussionmentioning
confidence: 99%
“…They have estimated that this factor is close to 0.82 in their studies. 8,9 We decided to analyse the data of our institute to review the methodology and local applicability of the graft weight/volume estimation techniques and attempt to formulate our own protocols which would lead to a more realistic graft weight/volume calculation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the implementation of the laparoscopic hepatic resection (13), the more liberal use of living-donor LT, even in Western countries (14), or finally the growing use of perfusion machines with the intent to improve the use of marginal grafts (15) all represent new opportunities for the physicians involved in the management of HCC patients waiting for LT.…”
mentioning
confidence: 99%